2016
DOI: 10.1159/000451060
|View full text |Cite
|
Sign up to set email alerts
|

Distinct in vitro Complement Activation by Various Intravenous Iron Preparations

Abstract: Background: Intravenous (IV) iron preparations are widely used in the treatment of anemia in patients undergoing hemodialysis (HD). All IV iron preparations carry a risk of causing hypersensitivity reactions. However, the pathophysiological mechanism is poorly understood. We hypothesize that a relevant number of these reactions are mediated by complement activation, resulting in a pseudo-anaphylactic clinical picture known as complement activation-related pseudo allergy (CARPA). Methods: First, the in-vitro co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 21 publications
0
54
0
1
Order By: Relevance
“…It is extremely unlikely that anyone reading this review was not taught that there is a serious risk of anaphylaxis with the use of parenteral iron. It is clear that this risk has been overstated for decades, with a big difference between the very rare serious allergic reactions which can lead to anaphylaxis (seen mainly in the 1970s and 1980s) and the uncommon, self‐limiting, minor hypersensitivity reactions that may be complement‐mediated or due to labile free iron in circulation . In the early 20th century, parenteral iron was thought to have prohibitive toxicity following the use of the intravenous (IV) colloidal ferric hydroxide, the carbohydrate core of which did not bind elemental iron tightly.…”
Section: Historical Overviewmentioning
confidence: 99%
“…It is extremely unlikely that anyone reading this review was not taught that there is a serious risk of anaphylaxis with the use of parenteral iron. It is clear that this risk has been overstated for decades, with a big difference between the very rare serious allergic reactions which can lead to anaphylaxis (seen mainly in the 1970s and 1980s) and the uncommon, self‐limiting, minor hypersensitivity reactions that may be complement‐mediated or due to labile free iron in circulation . In the early 20th century, parenteral iron was thought to have prohibitive toxicity following the use of the intravenous (IV) colloidal ferric hydroxide, the carbohydrate core of which did not bind elemental iron tightly.…”
Section: Historical Overviewmentioning
confidence: 99%
“…Based on the association of complement (C) activation with many of these adverse reactions, the term "complementactivation-related pseudoallergy" (CARPA) was introduced 1 and with time increasingly considered as a clinically relevant concept in liposomal chemotherapy and other areas of IV pharmacotherapy, [2][3][4][5] most recently in the medical use of nanoparticulate iron. 6,7 Nevertheless, a recent review questioned the pseudoallergic nature of these HSRs, the role of C, and the use of pigs as a relevant model. 8 The review concluded that "at present, current experimentally derived evidence is more in support of the rapid phagocytic response (RPR) hypothesis" (vs CARPA), essentially claiming that macrophage "bulimia" explains the HSRs independently of C activation.…”
Section: Introductionmentioning
confidence: 99%
“…Given that hypersensitivity reactions to IV iron are much less common than are seen with monoclonal antibodies or liposomal preparations, this is clearly much more difficult to demonstrate. Nevertheless, Hempel et al [5] , in this issue of Am J Nephrol , have attempted to provide some preliminary evidence that CARPA may be implicated in hypersensitivity reactions seen with IV iron, using a number of methods, including complement activation by 5 different IV iron preparations in vitro using functional complement assays, as well as studying complement activation in a group of hemodialysis patients receiving IV ferric carboxymaltose.…”
mentioning
confidence: 99%
“…The design of the experiments by Hempel et al [5] did not allow the authors to determine whether the complement activation seen was due to the iron itself or the carbohydrate shell. The expanding body of literature on nanoparticles [6] , however, suggests that it is more likely to be related to the carbohydrate shell.…”
mentioning
confidence: 99%
See 1 more Smart Citation